PUTUSAN PRAPERADILAN MENGENAI TINDAKAN PENANGKAPAN OLEH PETUGAS KEPOLISIAN OGAN KOMERINGRING ILIR TERHADAP YOGIE SINGA NEGARA: Decisions regarding Measures of Pretrial Arrest by Ogan Komering Ilir Police Officers to Suspect Yogie Singa Negara - Bagus Bara; Setiyono (Faculty of Law, Universitas Trisakti, 2025)
Law No. 8 of 1981 on Criminal Procedure regulates the implementation of arrests, but there are cases of arrests that are contrary to the Criminal Procedure Code, and this is reinforced by the Pre-Trial Decision of Kayuagung District Court No. 02/Pid.Pra/2018/PN.Kag. The formulation of the problem to be discussed, namely: Was the arrest by Ogan Komering Ilir (OKI) police officers of Yogie Singa Negara in accordance with KUHAP and Regulation of the Chief of the Indonesian National Police (Perkap) No. 14/2012 on the Management of Criminal Investigation? And whether the judge's decision to reject all of the applicant's requests in Kayuagung District Court Pretrial Decision No. 02/Pid.Pra/2018/PN.Kag is in accordance with KUHAP and Perkap No. 14/2012. This research uses normative legal methods, descriptive in nature, using secondary data. The result and conclution that the OKI police officers in carrying out the arrest of Yogie Singa Negara did not comply with the procedures in Article 18 paragraph (1) of KUHAP jo. Article 37 of Perkap No. 14/2012. The decision of the pre-trial judge of Kayuagung District Court No. 02/Pid.Pra/2018/PN.Kag was also deemed inappropriate, because it rejected entirely the petition of the applicant in the case.